The Political Classroom: Evidence and Ethics in Democratic Education - Hess, Diana E.; McAvoy, Paula (Routledge, 2014)
WINNER 2016 Grawemeyer Award in Education Helping students develop their ability to deliberate political questions is an essential component of democratic education, but introducing political issues into the classroom is pedagogically challenging and raises ethical dilemmas for teachers. Diana E. Hess and Paula McAvoy argue that teachers will make better professional judgments about these issues if they aim toward creating "political classrooms," which engage students in deliberations about questions that ask, "How should we live together?" Based on the findings from a large, mixed-method study about discussions of political issues within high school classrooms, The Political Classroom presents in-depth and engaging cases of teacher practice. Paying particular attention to how political polarization and social inequality affect classroom dynamics, Hess and McAvoy promote a coherent plan for providing students with a nonpartisan political education and for improving the quality of classroom deliberations.